DİNLERİN ŞEHİRLEŞME KABİLİYETİ - Şaban Düzgün (İslami İlimler Dergisi)
Urbanization is among by far the most serious questions of last decades related to religion. And it goes without saying that religion must with its severity face this issue and must inquire whether it has a capability of transforming the modern society with a due religious language. This is one facet of the issue. There still remain others to be answered such as whether urbanization has the same advantages and disadvantages for all religions or it depends, etc. This paper deals with the issue comprehensively but not in detail. It is in a way an outline for the studies to be carried out in the future to this cause.